2015
DOI: 10.1002/pc.23840
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thermoplastic veils on interlaminar fracture toughness of a glass fiber/vinyl ester composite

Abstract: The effects of two thermoplastic micro‐veils, polyamide (PA) and polyethylene terephthalate (PET) veil, on the interlaminar fracture toughness of a glass fiber/vinyl ester (GF/VE) composite were investigated. The veils incorporated into the composite as interleaving materials were first characterized via scanning electron microscopy (SEM), differential scanning calorimetry (DSC), contact angle and tensile testing in order determine the best candidate as toughening agent for the GF/VE composite. Composite lamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 23 publications
1
36
0
Order By: Relevance
“…Load, opening displacement, and crack length were recorded for the energy release rate ( G I ) calculation during the tests. The G I was calculated using the modified beam theory data‐reduction method, as follows: GI=FN3Pδ2b(a+|Δ|) where G I is the Mode‐I interlaminar fracture toughness, P is the applied load, δ is the load point displacement, b is the specimen width, a is the delamination length (crack length), Δ is a value that is determined experimentally by generating a least‐squares plot of the cube root of compliance ( C 1/3 ) as a function of delamination length, and F and N are the correction parameters to take into account a large displacement and the stiffening of the specimens by the loading blocks, respectively. These correction factors can be calculated using the following equations: F=1(310)(δa)2(32)(δta2) N=1(La)3(98)[1(La)2](δta2)935(δa)2 where t and L ′ are shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Load, opening displacement, and crack length were recorded for the energy release rate ( G I ) calculation during the tests. The G I was calculated using the modified beam theory data‐reduction method, as follows: GI=FN3Pδ2b(a+|Δ|) where G I is the Mode‐I interlaminar fracture toughness, P is the applied load, δ is the load point displacement, b is the specimen width, a is the delamination length (crack length), Δ is a value that is determined experimentally by generating a least‐squares plot of the cube root of compliance ( C 1/3 ) as a function of delamination length, and F and N are the correction parameters to take into account a large displacement and the stiffening of the specimens by the loading blocks, respectively. These correction factors can be calculated using the following equations: F=1(310)(δa)2(32)(δta2) N=1(La)3(98)[1(La)2](δta2)935(δa)2 where t and L ′ are shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…Various interleaf materials such as thermoplastic and thermoset films, nonwoven veils, and self‐same resin interleaf materials have been studied. Saz‐Orozco et al . investigated the effects of a polyamide (PA) veil on the interlaminar fracture toughness of a glass fiber–vinyl ester composite.…”
Section: Introductionmentioning
confidence: 99%
“…A minimum of five samples were tested in all assays. 16 All samples were acclimatized to the humidity and room temperature of our laboratory before mechanical and thermal analyses. The morphology of the modified red mud-reinforced phenolic foams was observed using a JEOL JSM-6700F scanning electron microscope.…”
Section: Characterization Techniquesmentioning
confidence: 99%
“…However, the effects of incorporating alternative reinforcement materials obtained from industrial waste, such as red mud, have not been reported. 15,16 Red mud, the industrial solid waste generated from alumina production, is an environmental pollutant with extremely severe effects. Approximately 0.8-1.8 tons of red mud is generated from the production of 1 ton of alumina.…”
Section: Introductionmentioning
confidence: 99%
“…Saz-Orozco, et al (2017) revealed the toughening properties of PA and polyethylene terephthalate (PET) veils. They found that the PET veil has better interfacial bonding but lower improvement of fracture toughness than the PA veil [19]. The increase in the interlaminar fracture toughness of interleaved composites is mainly due to the fiber bridging and the plastic zone ahead of the crack tip.…”
Section: Introductionmentioning
confidence: 99%